Analise da influência do ciclo menstrual sobre variáveis físicas e psicológicas em atletas universitárias de futsal feminino - COELHO, Bruno de Cassio (2024)
Objective: To analyze and understand the influence of the menstrual cycle (MC) on physical and psychophysiological variables in female university futsal athletes.Materials and Methods: The sample consisted of fourteen female recreational futsal athletes. All athletes were affiliated with regional leagues and participated in university-level competitions at regional, state, and national levels. The athletes had a mean age of 23.5 ± years, with a standard deviation of 4.25 years, a mean height of 162.7 ± centimeters, with a standard deviation of 4.65 centimeters, a mean body mass of 59.43 ± kilograms, with a standard deviation of 7.85 kilograms, and a mean body mass index of 22.43 ± (kg/m²), with a standard deviation of 2.53 (kg/m²). Data collection occurred at three different stages of the menstrual cycle: the first collection took place on the second day of menstruation, during the early follicular phase (EFP); the second ten days after the first collection, during the mid-follicular phase (MFP); and the third ten days after the second collection, during the mid-luteal phase (MLP), totaling a period of 20 days. Self-reported questionnaires on sleep quality, recovery status, and mood state were administered. Additionally, body mass index (BMI), flexibility, maximal 30m sprint test with splits at 10 and 20 meters, vertical jump tests, countermovement jump, and squat jump were assessed.Results: There were no significant differences between menstrual cycle phases for body mass index (BMI), sleep quality, flexibility, recovery status, maximal sprint time (10, 20, and 30 meters), and squat jump test. However, regarding mood state, athletes showed an increase (p<0.05) in the fatigue domain during the early follicular phase (EFP) compared to the mid- luteal phase (MLP). Additionally, during the mid-follicular phase (MFP) and MLP, an iceberg-shaped profile was identified, characterized by high levels of vigor associated with reduced levels of tension, depression, anger, fatigue, and confusion. However, this profile pattern was not observed during the EFP, as elevated levels of anger and fatigue were recorded. Regarding countermovement jump performance, a reduction (p<0.05) in athlete performance was observed during the EFP compared to the MFP and MLP. Conclusion: The increase in fatigue sensation during the early follicular phase (EFP), along with the absence of the iceberg-shaped profile pattern during this phase, combined with the reduction in countermovement jump performance, highlights the crucial importance of considering the menstrual cycle (MC) in the management of female sports training. It emphasizes the need to respect the individuality of each athlete throughout the menstrual cycle.